Institutional failures and missed opportunities: insights from engineering administrators on Native faculty hiring - Cruz Rios, Fernanda; El Asmar, Mounir; Grau, David; Parrish, Kristen (Frontiers in Education, 2026)
IntroductionPast studies have shown that the lack of diversity among STEM faculty is not due to the lack of qualified applicants, but to failures in strategies used to recruit and retain underrepresented faculty. Native peoples remain the most severely underrepresented group among engineering faculty in the United States, yet institutional hiring practices affecting their representation are rarely studied. This study examines institutional hiring practices related to Native faculty representation in engineering education.MethodsWe interviewed 22 deans and associate deans in engineering colleges across the United States to understand barriers to Native faculty hiring and institutional engagement with tribal communities. Using social capital theory and thematic analysis, we analyzed administrators’ perspectives on faculty hiring, diversity, and institutional relationships.ResultsMost administrators attributed underrepresentation to a limited applicant pool, while few acknowledged structural biases within hiring practices. Despite operating in states with large Native populations, most colleges lacked formal relationships with tribal communities and did not advertise positions in Native-serving outlets. We identified inconsistent diversity policies, overreliance on institutional reputation in hiring, and the absence of Native-centered research as systemic issues shaping faculty hiring.DiscussionThis study offers a framework for institutional change based on culturally responsive hiring, regional partnerships, and rethinking how Indigenous knowledge is valued in engineering education. Our findings suggest that reframing diversity as an institutional responsibility rather than a pipeline problem can help decolonize faculty hiring practices in STEM fields.